Asymétries directionnelles et fluctuantes en période périnatale : étude exploratoire dans les populations du passé - Caroline Partiot; Dominique Castex; Mark Guillon; Camille Noûs; Bruno Maureille; Frédéric Santos (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Directional asymmetry (the preferential expression of a character on one side rather than the other) and fluctuating asymmetry (minor, random and independent deviations from bilateral symmetry) are increasingly investigated in modern corpuses of deceased perinates, since they are involved in assessing preferential lateralization and developmental stability, respectively. However, few studies have examined these issues in perinates from past populations. Our study was conducted to investigate the absence or presence of these two types of asymmetry in an archaeological corpus, using an exploratory approach with a view to adapting existing protocols to the specific features of this osteological material. The study was carried out on a corpus of 116 individuals from three collections (Necropolis 8B-51 from Saï Island, Sudan, Classic Kerma period, the Blandy-les-Tours cemetery in the Paris Basin, 10th-13th centuries, and the Provins cemetery in the Paris Basin, 12th-18th centuries). The investigation produced an assessment of the methodological feasibility of these analyses for skeletonized remains and allowed to identify several variables expressing their asymmetries. We expect these preliminary results to initiate discussions on the use of this type of biological for osteobiographical analyses of immature individuals from past populations, and particularly as an estimator of developmental disturbances.